Resilience in a Traditional and Contemporary Context - Magdalena Anna Boczkowska (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
In this article out lines the koncept of resilience chich broadly relates to the adaptability of person, family or en tire communities in the face of adversity or traumatic events. The genesis of the conceptof resilience was pointed out. Norman Garmezy, Emmy Werner and Michael Rutter were pointed out as precusors to resilience research and a synthetic description of their research was also made. The considerations taken in this article are intended to show the complexity of the resilience construct Istel and the concepts related to it - positive adaptation, risk and protective factors. Cognitive possibilities and limitations in the use of the resilience koncept were also analyzed, emphasizing the Reed to establish uniform theoretical and empirical frameworks.